Alam Barzakh dalam Perspektif Hadis - Khusniyah Khusniyah; Muhammad Alif; Mus’idul Millah (Akhlak : Jurnal Pendidikan Agama Islam dan Filsafat, 2025)
The realm of barzakh is the first realm that humans enter after death. This realm is a realm of separation between the realm of this word and the realm of the afterlife. The discussion regarding the nature of barzakh seems to have never died. Disscussions related to nature cannot be separated from painting. Death is actually a frightening reality, and it will approach all humans. No one is able to resist it nor does anyone no one can afford it. And all of Adam’s children will meets his death, if he dies then he will live temporarily in the realm of barzakh. In that realm, he will wait until doomsday comes. Barzakh life is the gateway to the afterlife, in this world humans will receive rewards for the charity he has done while on earth. If you are bad, you will be punished and vice versa. The goodness that will last throughout this life will be bear sweet fruit in barzakh.